A pedagogy of hope after Paulo Freire - Le Grange, L (South African Journal of Higher Education, 2011)
In my review of the articles published in this issue of SAJHE I use the notion of ‘after’ in two senses: ‘in imitation of’ and ‘following in time’ (moving beyond) (Schad 2003, x). In the first instance I wish to assess the extent to which contributors have drawn on Paulo Freire’s concept of a ‘pedagogy of hope’ – how their work imitates that of Freire. In the second instance I wish to examine the extent to which authors engage critically with Freire’s work and perhaps help us in moving beyond Freire’s ideas. It is imperative that we maintain hope even when the harshness of reality may suggest the opposite (Freire in hooks 2003).